Analisis Implementasi Penyaluran Dana Zis Di Bmt Bina Dhuafa Bringharjo - Ivan Rahmat Santoso (Jurnal Akuntansi, 2014)
The Distribution Of Zakat, Donation, And Alms From Muslims As Early As Possible Should Be Channeled Effectivity As An Economic Empowerment Initiative Of The People